Productive Employee Training and Its Impact on Retention - Khadka, Ajaya Kumar; Khadka, Srijana (Nepal Journal of Multidisciplinary Research, 2024)
Background: The present research examines the financial aspects of efficacious employee training and its influence on employee retention in corporate environments. The study aims to assess how management assistance for employee retention, training and development, and future growth are related to performance reviews. Methods: Using a frequency distribution, the study looks at the demographic and social status of 297 participants who make up its sample. The reliability analysis demonstrates good consistency in the measurement scales. Results: Correlation analysis finds significantly positive correlations between the variables. A multiple regression analysis reveals a well-fitting model (R Square = 0.841), confirming the significant contribution of future growth, training, development, and management support to employees and performance reviews to explain variance in employee retention. Conclusion: The coefficient analysis emphasizes the significance of strategic approaches to improving employee retention and highlights the individual contributions of these factors. Novelty: This research adds to our understanding of the changing direction of employee retention. It offers valuable advice to firms looking to maximize managerial support and training strategies to cultivate a loyal and contented workforce.